2020
DOI: 10.3390/v12090915
|View full text |Cite
|
Sign up to set email alerts
|

Ebola Virus Disease Survivors Show More Efficient Antibody Immunity than Vaccinees Despite Similar Levels of Circulating Immunoglobulins

Abstract: The last seven years have seen the greatest surge of Ebola virus disease (EVD) cases in equatorial Africa, including the 2013–2016 epidemic in West Africa and the recent epidemics in the Democratic Republic of Congo (DRC). The vaccine clinical trials that took place in West Africa and the DRC, as well as follow-up studies in collaboration with EVD survivor communities, have for the first time allowed researchers to compare immune memory induced by natural infection and vaccination. These comparisons may be rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…Both B cell-and T cell-mediated responses are believed to be correlates of protection against EBOV infection, as indicated by high levels of neutralizing antibodies and antiviral T cells in human EVD survivors [2,14,15,46,47]. On the other hand, lymphopenia is a characteristic of EVD [16,[19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…Both B cell-and T cell-mediated responses are believed to be correlates of protection against EBOV infection, as indicated by high levels of neutralizing antibodies and antiviral T cells in human EVD survivors [2,14,15,46,47]. On the other hand, lymphopenia is a characteristic of EVD [16,[19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…Genetic factors, viral inoculum at infection, or regulatory differences might be the basis for retaining antibodies at a high concentration after viral clearance from the blood in most patients, whereas antibody concentrations of other survivors underwent a rapid and continuous decline. 20,28 For patients with an immunological response characterised by high, consistent, and durable antibody concentrations over time and who cross-reacted with multiple strains of Ebolavirus, the ability of these antibodies to be protective against a new infection with the same or a different Ebolavirus spp is still not precisely known, but might be determinant in the search for a pan-Ebola treatment or vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of EVD, a cohort study evaluating vaccination and EBOV infection has observed more efficient immunity in survivors than vaccinated volunteers. Higher neutralizing capacity, larger pool of neutralizing antibodies and elevated NK cell activation were observed in the survivors [ 276 ].…”
Section: Immunomodulatory Approaches For Combating Covid-19 and Evdmentioning
confidence: 99%